PERSENTASE SERANGAN Leucinodes orbonalis Gueene (Lepidoptera; Crambidae) PADA BUAH TERONG DI KELURAHAN WAILAN DAN KAKASKASEN DUA KECAMATAN TOMOHON UTARA - Elan K. Wowor; James B. Kaligis; Caroulus S. Rante (COCOS, 2017)
ABSTRACT The research aims to determine the percentage of larvae attack Leucinodes orbonalis Gueene on eggplant. This research was conducted in the Village Wailan and Kakaskasen Two North Tomohon sub district Tomohon. The study lasted five months, namely from March to August 2016. The research was conducted by survey on eggplant in North Tomohon Tomohon sub district, which is in the Village Wailan and Kakaskasen Dua each village taken one farmer's land. Sampling was done by the method diagonal slices are set out five sub-plot at the sampling site. Sampling was done by intervals of one week four times observation. Fruits are attacked calculated percentage amount. The results showed the average percentage of the highest attack in the village of Kakaskasen Dua is 28.17% while in the Village Wailan average percentage of attacks is only 6.85%.The test results of the analysis showed significant differences Significant 0,000 <0.05 then the corresponding basis for decision making in Test Independent Sample T-test, t can be concluded H0 and H1 accepted which means that there are differences in the percentage of fruit borer attacks at both locations. Keywords: percentage attack, Leucinodes orbonalis Gueene, fruit eggplant, eggplant